Analisis Peran Sistem Informasi Akuntansi Terhadap Akuntabilitas Pengelolaan Keuangan pada Badan Amil Zakat Nasional Provinsi Sumatera Utara - Putri widiya marpaung Nurhalimah; Muhammad Yafiz; Rahmat Daim Harahap (Indo-Fintech Intellectuals: Journal of Economics and Business, 2023)
This study aims to analyze the Role of Accounting Information Systems on Financial Management Accountability at the National Amil Zakat Board of North Sumatra Province. The research method used in this research is a qualitative method and this research approach uses descriptive analysis. The results of the research conclude that BAZNAS North Sumatra Province uses SIMBA (Zakat Information Management System) based on PSAK 109 to collect and distribute zakat, infaq and alms. The influence of the accounting information system on financial management at BAZNAS North Sumatra Province can be seen from the level of zakat receipts, and the implementation of accountability carried out by BAZNAS North Sumatra Province in financial management is in accordance with accountability indicators, namely implementing honesty and legal accountability, accountable procedures, programs accountable, and accountable regulations.